The Effect of Poverty Levels, Open Unemployment Rates on Crime Rates in Indonesia 2014-2024: a VECM Approach - Viona Retno Oktaviani; Ahmad Hazas Syarif; Alief Rakhman Setyanto (Journal of Trends Economics and Accounting Research, 2026)
The economy is one of the main triggers of high crime rates in Indonesia. This study aims to explore the extent of the relationship between poverty and open unemployment rates and crime rates in this country. This study was conducted using a quantitative approach, utilizing panel data and a VECM model to analyze long-term impacts. The data sources used were secondary data from reports by the Central Statistics Agency (BPS) and the Indonesian National Police (Polri). The results show that poverty has a significant positive impact on crime rates in Indonesia, as seen from the t-statistic being greater than the t-table, namely 13.9926 > 1.966378803 with a coefficient value of 34300.84. Similarly, open unemployment also has a significant positive impact as seen from the t-statistic which is greater than the t-table, namely 4.73350 > 1.966378803 with a coefficient value of 34616.26. Overall, these two factors, poverty and open unemployment, have a significant positive impact on crime rates in Indonesia, as indicated by an F-statistic greater than the t-table, namely 24.36384 > 1.96637883. These long-term findings indicate that high poverty rates and open unemployment rates can affect crime rates in Indonesia, while in the short term the opposite is true. This occurs because of survival mechanisms that utilize savings or government assistance. This study provides empirical evidence on the influence of poverty rates and open unemployment rates on high crime rates in Indonesia.